Cultural ergonomics : an exploration of culture on websites - Zanin-Lassila, Celia (2018)
For large organisations, websites are the primary means to reach an audience and (re)present their brand(s). By investigating the way, the UNICEF country offices choose to represent themselves in various countries through their websites, I analyze how one brand (re)presents itself through its web page in various countries. With the idea of determining whether or not there are differences in between the websites of the Country offices, if there were differences in the brand image presented and if these differences could be linked to cultural differences in the target market of the websites. Two main differences were identified, in the way the brand decided to place its audience vis a vis of the brand (inclusive or exclusive) and in the storytelling that was chosen. There were differences in the way the brand constructed its identity and presented itself to its audiences in different countries and some of these differences could be linked to cultural aspects of a country.